Pengembangan Instrumen Penilaian Sumatif Berbasis Project-Based Learning dalam Pembelajaran Seni Rupa di Sekolah Dasar - Pramistri Ambawono, Gancar; Pantiwati, Yuni (Jurnal PGSD, 2025)
The assessment of student learning outcomes in Visual Arts at the elementary school level often faces challenges such as low validity and reliability of assessment instruments, as well as teachers' limited ability to develop holistic project assessment rubrics. These issues affect the interpretation of students' learning outcomes. This study aims to develop a summative assessment instrument comprising multiple-choice questions, essay questions, and a project assessment rubric that is valid, reliable, and practical. The research employed a Research and Development (Borg & Gall, 1983) model involving needs analysis, design, validation, testing, and revision stages. The results showed item validity ranging from 0.45 to 0.53 and a reliability coefficient of 0.78, indicating good internal consistency. The mean combined score for multiple-choice and essay questions was 14.46, exceeding the "Excellent" threshold (≥13), indicating that students had achieved the expected competencies. The developed project assessment rubric also demonstrated good validation and was practical to use. Therefore, this instrument can serve as a solution to improve the quality of assessment in elementary schools, providing more holistic assessment and supporting meaningful learning.